Brand Community Knowledge, Involvement, Trust, Engagement, And Brand Loyalty (Glow Up Agents Community) - Andi Ade Rufiani RM; Maria Apsari Sugiat (Journal Research of Social Science, Economics, and Management, 2025)
The development of digital technology makes the brand community a key strategy to build loyalty in the beauty industry. This study examines the "Glow Up Agents" community by BHUMI Skincare, using the KITE (Knowledge, Involvement, Trust, Engagement) framework to analyze its influence on brand community engagement and brand loyalty. The PLS-SEM method was used with questionnaire data from active members to 184 respondents. The results showed that the entire hypothesized relationship was positively significant: the KITE dimension influenced member participation, which in turn increased brand loyalty. It affirms the important role of understanding, interaction, and trust. Practical advice includes community optimization, while academic advice recommends exploring additional variables for deeper understanding.